Improved method for specificity annotation shows a distinct evolutionary divergence among the microbial enzymes of the cholylglycine hydrolase family - Panigrahi, Priyabrata; Sule, Manas; Sharma, Ranu; Ramasamy, Sureshkumar; Suresh, C. G. (Microbiology-SGM, 2014)
Bile salt hydrolases (BSHs) are gut microbial enzymes that play a significant role in the bile acid modification pathway. Penicillin V acylases (PVAs) are enzymes produced by environmental microbes, having a possible role in pathogenesis or scavenging of phenolic compounds in their microbial habitats. The correct annotation of such physiologically and industrially important enzymes is thus vital. The current methods relying solely on sequence homology do not always provide accurate annotations for these two members of the cholylglycine hydrolase (CGH) family as BSH/PVA enzymes. Here, we present an improved method [binding site similarity (BSS)-based scoring system] for the correct annotation of the CGH family members as BSH/PVA enzymes, which along with the phylogenetic information incorporates the substrate specificity as well as the binding site information. The BSS scoring system was developed through the analysis of the binding sites and binding modes of the available BSH/PVA structures with substrates glycocholic acid and penicillin V. The 198 sequences in the dataset were then annotated accurately using BSS scores as BSH/PVA enzymes. The dataset presented contained sequences from Gram-positive bacteria, Gram-negative bacteria and archaea. The clustering obtained for the dataset using the method described above showed a clear distinction in annotation of Gram-positive bacteria and Gram-negative bacteria Based on this clustering and a detailed analysis of the sequences of the CGH family in the dataset, we could infer that the CGH genes might have evolved in accordance with the hypothesis stating the evolution of diderms and archaea from the monoderms.